Promoção de saúde e participação social: o modelo de atenção básica do Sistema de Saúde Brasileiro - Breno Augusto Fontes; Rogério de Lima; Jorge Alexandro de Lima (Ciências Sociais Unisinos)
The health reform in Brazil has introduced a number of management mechanisms which incorporate popular participation, and, on the other hand, emphasis on health promotion. In this article we aim to focus on a health practice that involves popular participation, which has been carried out since the introduction of community health programs, at fi rst with HCAP (Health Community Agents Programs), and later with FHP (Family Health Program). Since the intermediation established between the community and the health workers with the community health agents, we analyze this practice as an instrument of territorial and community inclusion within health policies. With an empirical study in four Brazilian cities we have evaluated the adequacy of the referred model to different socio-cultural contexts, as well as the obstacles to the achievement of participatory democracy ideals.